Penulisan media massa - Faridah Ibrahim; Normah Mustaffa; Mohd Rajib Ab Ghani; Universiti Malaysia Perlis (Kangar : Penerbit Universiti Malaysia Perlis, 2017)
On journalism and mass media authorship.
Includes bibliographical references (pages 312-316) and index.
Keywords: Mass media -- Authorship; Journalism -- Authorship